Irony, body and disease in Juan del Valle and Caviedes - Escobar Tapia, Héctor Omar (2023)
Two poems by Juan del Valle y Caviedes are analyzed in this article. Caviedes, a poet who was active in the 17th century, is characterized by his use of irony to criticize the medical practices of his time and for being the initiator of Creole poetry in Peru. Semiotic categories have been employed to explain the mechanisms of irony and the importance of the body in Caviedes’ poetry. The proposed explanation is divided into two points: firstly, it argues that the poetic self employs irony and polyphony to critique medical practices; and secondly, it emphasizes the significance of the body in Caviedes’ poetry. The article concludes that the body is the radical condition of signification in Caviedes’ poetry.